The Pedagogy of “Fear of Hell”: Analyzing Symbolic Violence in Primary Education - Putri, Rina Oktafia; Fatah, Ahmad (Program Studi Tadris IPS Fakultas tarbiyah IAIN Kudus, 2026)
This research aims to analyze the pedagogy of